Fluktuasi Harga Minyak Global dan Dampaknya Terhadap Ekspor Migas Indonesia - Edy Soesanto; Matthew Tamima; A Raaf Dasuqi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Economic growth is a critical aspect of economic policy in any country or economic system. According to data from Indonesia's Central Statistics Agency, the country's economic growth has fluctuated over the years. Factors influencing a nation's economic growth include export activities and inflation. The oil and gas (O&G) industry plays a strategic role in supporting national economic growth by contributing to Gross Domestic Product (GDP), state revenue, and job creation. This study aims to analyze the impact of the O&G industry on the national economy and provide perspectives on future challenges and opportunities. Using both quantitative and qualitative approaches, secondary data such as government financial reports, industry statistics, and policy analyses were utilized to assess the sector's contributions across various economic dimensions. The findings indicate that the O&G sector remains one of the primary sources of state revenue, despite significant challenges posed by declining reserves and volatile global oil prices. On the other hand, energy diversification and technological development present opportunities to enhance efficiency and sustainability in this sector.